THE INTERNALIZATION OF BANJARAN CULTURAL CHARACTER VALUES IN MUSTAFAWIYAH ISLAMIC BOARDING SCHOOL, PURBABARU - Salabi, Agus Salim; Prasetyo, Muhammad Anggung Manumanoso (State Islamic University North Sumatra, 2022)
Abstract: Islamic boarding school is connected to the execution of ideas through organizational culture. The term Banjaran culture is referred to the significant knowledge which can develop students' attitudes and behaviors. Following the assumption of reflective practice, this study critically investigates the suitability of cultural values. Data were collected from the deputy secretary, Mr. Mukhlis Lubis as the representatives of school leaders, head caregivers, and senior students using a qualitative paradigm as well as phenomenological methodologies. The results showed that internalization occurred at several managerial levels. Meanwhile, the Banjaran culture is accomplished as a distinguishing element, a mutual commitment-forming, and helps to generate a stable social structure, as well as develop students' characters. The value of independence, creativity, entrepreneurial motivation, religiosity, communication, social interaction, mental and physical resilience, moderation, tolerance, and ukhuwah (friendship and kinship) are parts of the qualities created by its internalization.Keywords: Banjaran culture: Islamic boarding school culture: character building, Musthafawiyah